Intra-abdominal pressure and mechanical artificial ventilation. Arnaldo Milián Castro Hospital. 2014-2015 - Glenda Figueredo Rodríguez; David Alejandro Rodríguez-Rojas; Jarvis Céspedes Cárdenas; Nabil Ghaddar Fuentes; David Wilfredo Suárez Prieto (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: The abdominal cavity and the thoracic cage are separated by the diaphragm; therefore, the variations in the pressures within one of them have an effect on the pressures of the other. At present, intra-abdominal hypertension is a frequent entity in the critically ill patient, which constitutes an important risk factor for complications and mortality since it influences on different organs and systems. Objective: To relate intra-abdominal pressure with mechanical artificial ventilation pressures and parameters of respiratory, cardiovascular and renal function. Material and Methods: A descriptive prospective study of intra-abdominal pressure was conducted in patients undergoing mechanical ventilation with clinical and surgical diseases in the Intensive Care Units of the Arnaldo Milán Castro Hospital, during the period between January 2014 until December 2015.  Results:  Clinical patients with high values of airway pressures showed higher values of intra-abdominal pressure, and those post-surgical patients who presented with high levels of pressure inside the abdomen indicated the highest values of peak and average pressure recorded in the mechanical ventilator.   Conclusions: Mean arterial pressure, diuretic rate and peripheral oxygen saturation decreased, whereas the central venous pressure, the partial pressure of carbon dioxide in blood, and creatinine increased due to raises in pressure within the abdomen. Keywords: Artificial respiration, transcutaneous blood gas monitoring, arterial pressure, diuresis,             abdomen.